2008
DOI: 10.1016/j.ejcts.2007.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve in videothoracoscopic thymectomy: how many operations and in which situations?

Abstract: A chest surgeon can have a high success rate in videothoracoscopic thymectomy (98%) after 60 operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…In the past, many studies have analysed the learning curve for different surgical techniques (12,(19)(20)(21)(22)(23)(24). Generally speaking, a learning curve is considered to have been overcome when the monitored outcome indicators reach a steady state (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, many studies have analysed the learning curve for different surgical techniques (12,(19)(20)(21)(22)(23)(24). Generally speaking, a learning curve is considered to have been overcome when the monitored outcome indicators reach a steady state (20).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies20, 21 have demonstrated that CUSUM analysis is a useful tool for quantifying the duration of a training regimen, providing an early indication of performance as well as individual difficulties or failure to achieve competence. The method is practical, simple to apply, easy to introduce and has proved popular with trainees in some medical and surgical specialties19, 26. This method determines whether trainees have reached the acceptable predefined level of performance.…”
Section: Discussionmentioning
confidence: 99%
“…Toker et al reported a correlation between the operation time and BMI; however, we did not detect any such correlation in the present study. 18) We also performed single-port thymectomy, which was previously reported by Suda et al 19) Not setting a thoracic port seemed attractive to us, as this would likely reduce the postoperative pain although two-port thymectomy would have likely reduced the postoperative pain compared with the lateral approach. Unfortunately, we did not obtain any data regarding the postoperative pain on a numerical rating scale in the present study.…”
Section: Disclosure Statementmentioning
confidence: 99%